2015
DOI: 10.1177/2333721415598432
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health Among Very Old People in European Countries

Abstract: Objectives: To explore and gain insight into factors related to self-rated health (SRH) among very old people in two European countries. Methods: The study was based on Latvian (n = 301) and Swedish (n = 397) data from the baseline of the Enabling Autonomy, Participation, and Well-Being in Old Age: The Home Environment as a Determinant for Healthy Ageing Survey Study. Besides descriptive statistics, ordinal regression analysis was used to analyze demographic, physical and mental health-related, functional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 43 publications
4
7
1
1
Order By: Relevance
“…Incidence of impaired physical mobility increases with age [5]. Some previous studies have investigated physical mobility and SRH and have found an association [15,23]. There was a strong association between impaired physical mobility and SRH in our study, which highlights the importance of improving and maintaining physical mobility among the oldest-old.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Incidence of impaired physical mobility increases with age [5]. Some previous studies have investigated physical mobility and SRH and have found an association [15,23]. There was a strong association between impaired physical mobility and SRH in our study, which highlights the importance of improving and maintaining physical mobility among the oldest-old.…”
Section: Discussionsupporting
confidence: 66%
“…The relative stability found in SRH may indicate that with increasing age older people adapt to their worsening health condition [17] or it may be due to higher mortality and higher non-response among the participants with poorest SRH [28]. Yet, relatively high proportions of good SRH among the oldest-old have even been reported in other studies [19,21,23].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The Home Environment as a Determinant for Healthy Aging" based on Latvian and Swedish data showed that poor perceived mobility was associated with poor SRH, while education was a determinant of SRH only for the Latvian sample. Age was not a significant determinant for either population [50]. Our results showed that for dentate participants, age was significantly associated with SROH and SWL (p=0.001); however, the findings for SRH were not significant, in accordance with the Latvian and Swedish data, as reported by Harschel et al, 2015.…”
Section: Discussionsupporting
confidence: 52%
“…Age was not a significant determinant for either population [50]. Our results showed that for dentate participants, age was significantly associated with SROH and SWL (p=0.001); however, the findings for SRH were not significant, in accordance with the Latvian and Swedish data, as reported by Harschel et al, 2015. In the present study, education, income and occupation were statistically significantly associated with both SROH and SRH (p=0.01).…”
Section: Discussionsupporting
confidence: 52%